2018
DOI: 10.2134/jeq2017.06.0234
|View full text |Cite
|
Sign up to set email alerts
|

Supply and Transport Limitations on Phosphorus Losses from Agricultural Fields in the Lower Great Lakes Region, Canada

Abstract: Phosphorus (P) mobilization in agricultural landscapes is regulated by both hydrologic (transport) and biogeochemical (supply) processes interacting within soils; however, the dominance of these controls can vary spatially and temporally. In this study, we analyzed a 5-yr dataset of stormflow events across nine agricultural fields in the lower Great Lakes region of Ontario, Canada, to determine if edge-of-field surface runoff and tile drainage losses (total and dissolved reactive P) were limited by transport m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 68 publications
5
38
0
Order By: Relevance
“…There would also be considerable dilution from shallow groundwater and generally enhanced contact between P and subsoils. Greater contact between infiltrating water and subsoils is likely to result in enhanced soil P sorption and attenuation prior to water discharge from tiles (Reid et al, 2012; Andersson et al, 2013; Plach et al, 2018a). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There would also be considerable dilution from shallow groundwater and generally enhanced contact between P and subsoils. Greater contact between infiltrating water and subsoils is likely to result in enhanced soil P sorption and attenuation prior to water discharge from tiles (Reid et al, 2012; Andersson et al, 2013; Plach et al, 2018a). …”
Section: Discussionmentioning
confidence: 99%
“…For example, P losses in tile drainage can be reduced through tillage (Williams et al, 2016; King et al, 2015b) and subsurface P placement (Grant et al, 2019a,b; Williams et al, 2018). Furthermore, studies have demonstrated P supply limitation in tile drainage (Plach et al, 2018a) and suggested that subsurface biogeochemistry can also play a significant role on P retention by subsoils (Plach et al, 2018b; Andersson et al, 2013; Djodjic et al, 2004). Although examining the effects of specific land management on tile P mobilization was beyond the scope of the current study, it should be acknowledged that different management practices were used across the sites and years in the current study, including tillage and no‐till, surface broadcasting, and subsurface placement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, tile drains may increase edge‐of‐field losses of P, exacerbating water quality issues in the Red River valley. In other clayey landscapes, increased runoff and nutrient losses through tile drains have been linked to preferential flow through macropores and desiccation cracks, which are active during frozen as well as thawed conditions (Smith et al, 2015; Plach et al, 2018; Grant et al, 2019). However, this has not been assessed in the Vertisolic soils found within the Red River valley.…”
mentioning
confidence: 99%